Pascu-Type Harmonic Functions with Positive Coefficients Involving Salagean Operator. (6th April 2014) - Vijaya, K.; Murugusundaramoorthy, G.; Kasthuri, M.
Abstract : Making use of a Salagean operator, we introduce a new class of complex valued harmonic functions which are orientation preserving and univalent in the open unit disc. Among the results presented in this paper including the coeffcient bounds, distortion inequality, and covering property, extreme points, certain inclusion results, convolution properties, and partial sums for this generalized class of functions are discussed.